Public pages : reading along the Latin American streetscape - Schwartz, Marcy E., 1958- (University of Texas Press, 2018)
Public reading programs are flourishing in many Latin American cities in the new millennium. They defy the conception of reading as solitary and private by literally taking literature to the streets to create new communities of readers. From institutional and official to informal and spontaneous, the reading programs all use public space, distribute creative writing to a mass public, foster collective rather than individual reading, and provide access to literature in unconventional arenas. The first international study of contemporary print culture in the Americas, Public Pages reveals how recent cultural policy and collective literary reading intervene in public space to promote social integration in cities in Colombia, Argentina, Brazil, Mexico, and Chile. Marcy Schwartz looks at broad institutional programs such as UNESCO World Book Capital campaigns and the distribution of free books on public transportation, as well as local initiatives that produce handmade books out of recycled materials (known as cartoneras) and display banned books at former military detention centers. She maps the connection between literary reading and the development of cultural citizenship in Latin America, with municipalities, cultural centers, and groups of ordinary citizens harnessing reading as an activity both social and literary. Along with other strategies for reclaiming democracy after decades of authoritarian regimes and political violence, as well as responding to neoliberal economic policies, these acts of reading collectively in public settings invite civic participation and affirm local belonging.